2019
DOI: 10.1017/glj.2019.82
|View full text |Cite
|
Sign up to set email alerts
|

The Dialectics Between Constitutional Identity and Common Constitutional Traditions: Which Language for Cooperative Constitutionalism in Europe?

Abstract: This Article revisits the role and function of constitutional identity and common constitutional traditions and claims that the latter have had an increasingly stronger influence on the process of European integration—more than may appear at first sight. In addition, the relevance of common constitutional traditions has not been undermined but, on the contrary, strengthened by the emergence of fundamental rights in EU law and the subsequent conferral of binding force on the Charter of Fundamental Rights. Const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This umbrella term was first used in the Internationale Handelsgesellschaft judgment, 12 in which the Court explained that 'The protection of such rights, whilst inspired by the constitutional traditions common to the Member States, must be ensured within the framework of the structure and objectives of the Community.' 13 With this dictum, the Court masterfully appeased national constitutional courts' critiques 14 by underlying the existence of a shared 'tradition' concerning the protection of fundamental rights in the Member States, to be taken into consideration also at the Community level. At the same time, Internationale Handelsgesellschaft indicated that the CJEU was seeking to construct the Community's autonomy in the fundamental rights field, as the application of fundamental rights had to be ensured 'within the framework of the structure and objectives of the Community.'…”
Section: Common Constitutional Traditions In the Eu Legal Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…This umbrella term was first used in the Internationale Handelsgesellschaft judgment, 12 in which the Court explained that 'The protection of such rights, whilst inspired by the constitutional traditions common to the Member States, must be ensured within the framework of the structure and objectives of the Community.' 13 With this dictum, the Court masterfully appeased national constitutional courts' critiques 14 by underlying the existence of a shared 'tradition' concerning the protection of fundamental rights in the Member States, to be taken into consideration also at the Community level. At the same time, Internationale Handelsgesellschaft indicated that the CJEU was seeking to construct the Community's autonomy in the fundamental rights field, as the application of fundamental rights had to be ensured 'within the framework of the structure and objectives of the Community.'…”
Section: Common Constitutional Traditions In the Eu Legal Landscapementioning
confidence: 99%
“…Yet exploring the role of common constitutional traditions in shaping effective judicial protectionthe primus inter pares among the general principles of EU lawbrings focus to the heart of the conundrum of the EU: although it is an autonomous legal system, it is inevitably shaped by the legal concepts and traditions existing in its Member States. What is more, while it has been established that common constitutional traditions remain an evolutionary force for EU law, 4 in so far as they shape EU general principles, recent developments highlight two tensions between national constitutional traditions and EU standards of effective judicial protection enshrined in the homonymous principle.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of this conceptual overlap, the evolution of existing national constitutions and the blossoming of a new European (non-)constitution were portrayed as two sides of the same coin -hence, credited with identical legitimacy. The idea behind this theory was that both processes originated from certain values shared by all Member States, which pointed to the rise of common constitutional traditions (Fichera & Pollicino, 2019: 1097. The Community's constitutionalisation was being achieved as the outcome of a manifold, converging process of constitutional change involving the States (Muñoz Machado, 1993: 59) and the supranational construct at once.…”
Section: Constitutional Ripeness: the Wandel-verfassungmentioning
confidence: 99%
“…Legal doctrine in Latvia has gone much further than that in finding the true content of the Rule of Law and connects it directly with the notion of the general principles of law. 3 The author of this paper suggests to put the general principles of law in the centre of the discussion on what the common constitutional traditions are, in connection with the legal arrangement of the state which is based on the Basic Norm -democracy and the Rule of Law -as all the Member States of the European Union are -and answer to the above questions would come straightforward from the meaning and application practices of the term "general principles of law" and that for sure would include all the aforementioned elements of the Rule of Law agreed on by the Venice Commission, but also even some more legal provisions.…”
Section: Introductionmentioning
confidence: 99%